The Politics of WTO Enforcement Mechanism - Chang, Pao Li (Institutional Knowledge at Singapore Management University, 2004)
This paper attempts to develop a formal economic framework to analyze the influences of domestic political considerations by democratic governments in shaping the WTO enforcement outcomes following a violation ruling against the defendant. Since a different mix of import and export sectors in the defendant and complainant country will benefit from the various potential enforcement outcomes, they become competing forces which steer the strategic interactions between the disputing governments. The results of the paper illustrate the complainant's strategy in selecting the retaliation list, and the likelihood of the defendant's compliance or compensation in response to the proposed or foreseeable retaliation, given the political and economic environments on both sides of the disputing parties. This paper also captures the possibility of enforcement failures under the current WTO dispute settlement procedure, where the complainant does not have enough retaliation capacity to induce compliance or some form of compensation from the defendant.